2020
DOI: 10.1177/2374373520916030
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reports of Night Noise in Hospitals Are Associated With Unplanned Readmissions Among Older Adults

Abstract: Objective: Sleep disturbance is a key contributor to posthospital syndrome; a transient period of vulnerability following discharge from hospital. We sought to examine the relationship between patient-reported hospital quietness at night, via a validated survey, and unplanned hospital readmissions among hospitalized seniors (ages 65 and older) in Alberta, Canada. Design: Retrospective, cross-sectional analysis of survey responses, linked with administrative inpatient records. Setting: Using the Canadian Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
7
0
Order By: Relevance
“… 38 This has also been demonstrated in Canada where patient-reported quietness in their hospital environment was associated with a decrease in 30-day and 90-day readmission rates. 39 Our research adds to this evidence in quantifying an association between patients’ perceptions of rest and unplanned readmissions. This finding provides a rationale for hospitals to ensure that patients receive adequate rest and sleep throughout their hospital stay.…”
Section: Discussionmentioning
confidence: 79%
“… 38 This has also been demonstrated in Canada where patient-reported quietness in their hospital environment was associated with a decrease in 30-day and 90-day readmission rates. 39 Our research adds to this evidence in quantifying an association between patients’ perceptions of rest and unplanned readmissions. This finding provides a rationale for hospitals to ensure that patients receive adequate rest and sleep throughout their hospital stay.…”
Section: Discussionmentioning
confidence: 79%
“…In one study, we found that a lack of patient involvement in their care decisions and not receiving written discharge instructions were associated with unplanned readmission to hospital [ 42 ]. Among older adults, we observed that those who reported night noise in their hospital environment had higher odds of being readmitted to hospital [ 43 ]. In another study among adults, we explored use of the 3-item Care Transitions Measure.…”
Section: Resultsmentioning
confidence: 99%
“…Association with patient-reports of night noise in hospitals with unplanned readmissions among older adults [43] Examine the relationship between patient-reported hospital quietness at night, via a validated survey, and unplanned hospital readmissions among hospitalized seniors (ages 65 and older).…”
Section: Cpes-ic Dadmentioning
confidence: 99%
“…Noise originates from machine notifications, patient care alarms (bed alarm, call bell, codes), care staff, and other patients 64. High levels of noise are correlated with sleep disturbance, longer length of stay (LOS), and unplanned readmissions 65,66…”
Section: Measurements Of Sleep Disturbancesmentioning
confidence: 99%
“…64 High levels of noise are correlated with sleep disturbance, longer length of stay (LOS), and unplanned readmissions. 65,66 Overhead lights in the hospital are kept at a constant level of brightness throughout most of the working days; designed to provide an optimal environment for health care providers to function. 67 Exposure to light close to bedtime can negatively impact the quality of sleep.…”
Section: Environmental Factorsmentioning
confidence: 99%